Aberrant gene expression in the diagnosis of childhood leukemias not characterized by -involved cytogenetic abnormalities - Maria Adamaki; Spiros Vlahopoulos; George I Lambrou; Athanasios G Papavassiliou; Maria Moschovi (Tumor Biology)
The AML1 ( acute myeloid leukemia 1 ) gene, a necessary prerequisite of embryonic hematopoiesis and a critical regulator of normal hematopoietic development, is one of the most frequently mutated genes in human leukemia, involving over 50 chromosome translocations and over 20 partner genes. In the few existing studies investigating AML1 gene expression in childhood leukemias, aberrant upregulation seems to specifically associate with AML1 translocations and amplifications. The aim of this study was to determine whether overexpression also extends to other leukemic subtypes than the ones karyotypically involving AML1 . We use quantitative real-time polymerase chain reaction methodology to investigate gene expression in 100 children with acute leukemias and compare them to those of healthy controls. We show that in childhood acute lymphoblastic leukemia, AML1 gene overexpression is associated with a variety of leukemic subtypes, both immunophenotypically and cytogenetically. Statistically significantly higher transcripts of the gene were detected in the acute lymphoblastic leukemia group as compared to the acute myeloid leukemia group, where AML1 overexpression appeared to associate with cytogenetic abnormalities additional to those that engage the AML1 gene, or that are reported as showing a “normal” karyotype. Collectively, our study shows that AML1 gene overexpression characterizes a broader range of leukemic subtypes than previously thought, including various maturation stages of B-cell acute lymphoblastic leukemia and cytogenetic types additional to those involving the AML1 gene.